Diagnostics of Severe Fever with Thrombocytopenia Syndrome – Disease, Caused by Novel Phlebovirus - T. E. Sizikova; V. N. Lebedev; N. V. Boyarskaya; S. V. Borisevich (Проблемы особо опасных инфекций, 2016)
In 2009, a novel virus, named severe fever with thrombocytopenia syndrome (SFTS) virus, was isolated from a patient in China. The illness caused by this novel virus is characterized by a sudden onset of fever and respiratory or gastrointestinal disorders, followed by progressive thrombocytopenia and leucocytopenia, the case-fatality rate amounting to 6–30 %. Genomic sequencing of the isolated agent indicated that the SFTS virus constituted a new (third) group of Phlebovirus genus, Bunyaviridae family. Presently, different means for specific diagnostics of SFTS (real-time reverse transcription polymerase chain reaction, indirect fluorescent antibodies method, enzyme-linked immune-sorbent assay) are developed. Constructing of diagnostic kits, basic characteristics of methods for determination of causative agent of infection or specific antibodies against it are considered in this review.